Intraspecific Variation of Sargassum polycystum C. Agardh from Sundaland, Indonesia, Based on Morphological Characters - Nurmiyati Nurmiyati; Sutarno Sutarno; Rina Sri Kasiamdari; Purnomo Purnomo (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2026)
Sargassum polycystum C. Agardh is a keystone species in tropical waters' ecosystems and is characterized by high morphological plasticity. The Sundaland region, which consists of a wide range of oceanographic conditions, offers diverse microhabitats that may promote complex patterns of phenotypic variation. However, studies on intraspecific variation of S. polycystum in this region are still limited. Therefore, this study aimed to examine the morphological variation of S. polycystum at ten locations in Sundaland and identify key diagnostic characters that drive population differentiation. A total of 200 individuals were analyzed using 37 morphological characters. Phenotypic relationships were mapped using UPGMA cluster analysis with Gower Similarity Index and Principal Component Analysis (PCA). The results showed relatively homogeneous water chemistry parameters across sites, whereas physical characteristics varied among locations. Quantitative traits were uniform across populations (p = 0.99), suggesting growth stability associated with nutritional homogeneity. UPGMA analysis separated populations into two groups based on habitat typology. PCA showed that phylloid margin shape and vesicle morphology were the main diagnostic characters. Intertidal populations were characterized by serrated phylloids and densely spined primary branches, which likely function as drag-reducing mechanisms, whereas subtidal populations developed winged vesicles to enhance buoyancy. These findings suggest a segregation mechanism, where morphological variation in S. polycystum is driven by phenotypic plasticity to environmental physical constraints, regardless of water chemistry. A comprehensive understanding of these microhabitat-based ecological adaptation patterns provides important fundamental information for resolving macroalgal taxonomy, while simultaneously supporting sustainable coastal resource management and conservation strategies in tropical waters.